Accurate predictions of spectroscopic and molecular properties of the NTe molecule. (November 2017) - Liu, Siyuan; Zhang, Xiaomei; Zhai, Hongsheng; Liu, Yufang
Highlights: Total 28 Λ-S states of the NTe molecule have been calculated for the first time. The polarity of the ground state for NTe is determined to be N δ− Te δ+ . The SOC effects make the lowest 10 Λ-S states split into 30 Ω states. The Ω-state transitions borrow TDMs from the spin-allowed Λ-S transitions via SOC. Abstract: The entire 28 Λ-S electronic states correlated to four dissociation limits of the NTe molecule have been reliably characterized for the first time. The potential energy curves (PECs) and wavefunctions of these Λ-S states are calculated using the multi-reference configuration interaction plus Davidson correction (MRCI+Q) approach, with all-electron correlation-consistent basis sets at quadruple-zeta level. The spectroscopic constants of the bound Λ-S states are determined from the PECs, and the excellent agreement with previous work is derived. By analyzing the dipole moment, the polarity of the ground state for NTe is determined to be N δ− Te δ+, which is contrary to the case of NO. The spin-orbit coupling (SOC) effect is included when the state interaction method is applied. The SOC effect is found to be substantial for the NTe molecule, which makes the lowest 10 Λ-S states split into 30 Ω states. The X 2 Π states split into two Ω states including X 2 Π1/2 (X1 1/2) and X 2 Π3/2 (X2 3/2), and the corresponding SOC splitting is computed to be 1975 cm −1 (0.245 eV). Analysis of Λ-S compositions for the Ω-state wavefunction indicates the strong interaction among the Λ-S states. Additionally, the transition properties of the Ω-state transitions 1/2(2)-X1 1/2, 1/2(4)-X1 1/2, 3/2(10)-X2 3/2, and 5/2(1)-X2 3/2 were predicted. These transitions are all mainly from the spin-forbidden Λ-S transitions, but their transition dipole moments arise from those of the spin-allowed Λ-S transitions via the SOC effect. Accordingly, these transitions have quite long radiative lifetimes that are at the microsecond (ms) level.